2011
DOI: 10.2486/indhealth.ms1271
|View full text |Cite
|
Sign up to set email alerts
|

Association between Night-shift Work and Serum 25-hydroxyvitamin D Levels in Japanese Male Indoor Workers: A Cross-sectional Study

Abstract: Although low vitamin D status resulting from night work is a suspected cause of various health disorders, few studies have investigated the association between night-shift work and vitamin D status. Here, we examined serum 25-hydroxyvitamin D (25OHD) levels in 19 Japanese indoor workers, including night-shift workers, in blood samples collected at the annual medical checkup (late July) in a metal tool factory. Analyses were finally restricted to 14 male workers (33-59 yr) in 3 groups: fixed daytime work (n=6),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
5
19
1
3
Order By: Relevance
“…Melatonin suppression, decreased vitamin D levels, or lifestyle disturbances (absent in mice) cannot account for the enhanced cancer risk in animals kept under LD inversion conditions: (1) p53 R270Hª/+ WAPCre mice (FVB background) are melatonin deficient; (2) neither CRD mice nor controls were exposed to sunlight, and we found no difference in 25-hydroxy-vitamin D between groups. This is consistent with a study in night shift workers, which found no difference in vitamin D levels between fixed daytime workers, rotating shift workers without night shift, and rotating shift workers with night shift [22]. (3) Lifestyle factors did not differ (amount of food intake) in the LD inversion mice and the controls or were absent (e.g., breastfeeding, smoking).…”
Section: Discussionsupporting
confidence: 91%
“…Melatonin suppression, decreased vitamin D levels, or lifestyle disturbances (absent in mice) cannot account for the enhanced cancer risk in animals kept under LD inversion conditions: (1) p53 R270Hª/+ WAPCre mice (FVB background) are melatonin deficient; (2) neither CRD mice nor controls were exposed to sunlight, and we found no difference in 25-hydroxy-vitamin D between groups. This is consistent with a study in night shift workers, which found no difference in vitamin D levels between fixed daytime workers, rotating shift workers without night shift, and rotating shift workers with night shift [22]. (3) Lifestyle factors did not differ (amount of food intake) in the LD inversion mice and the controls or were absent (e.g., breastfeeding, smoking).…”
Section: Discussionsupporting
confidence: 91%
“…Daily workers were defined as subjects working only on daylight hours (9 a.m. to 5 p.m.), and night-shift workers as subjects working on nocturnal hours at least twice a week. As it was expected, but contrary to the previous Japanese study by Itoh et al (2011), low 25-OH vitamin D serum levels are associated with shift work. We interpret this phenomenon as the effect of a general higher open-air exposure in daily workers.…”
Section: Discussioncontrasting
confidence: 82%
“…In fact, we conducted the current study during the month of April, thus avoiding a confounding factor: at the end of winter, sun radiation in Northern Italy is not able to convert cutaneous vitamin D precursor into the biological active form and cannot attenuate the difference of vitamin D concentration between night and daily workers (Itoh et al, 2011;Hilger et al, 2014). Besides, dairy products are not supplemented with vitamin D, since Italian public health authorities do not recommend it.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bunun yanında, Itoh ve ark. [19] kapalı ortamda çalışan Japon erkeklerini, gündüz çalışan işçiler ve gece çalışan işçiler ile 25-hidroksivitamin D 3 seviyesi için karşılaştırmala-rına rağmen bu gruplar arasında istatistiksel olarak anlamlı farklılık tespit etmemişlerdir.…”
Section: Gereç Ve Yöntemlerunclassified